Learning Tools Based on Outcome Based Learning in Science Courses of Postgraduate Primary School Teacher Education Programs - I Komang Wahyu Wiguna; Ni Nyoman Lisna Handayani (Universitas Pendidikan Ganesha, 2024)
Curriculum development in higher education currently requires implementing the independent campus program. The independent campus program requires universities to be able to implement an output-based curriculum or outcome-based education. This research aims to analyze the need to develop learning tools based on outcome-based learning, especially in the core scientific subjects of primary school teacher education postgraduate programs. This research uses a descriptive qualitative approach. Data collection used questionnaire techniques, observation, and interviews with 14 lecturers as respondents. This research produced three important findings. First, all lecturers prepare learning tools before carrying out lectures. Second, 57.1% of lecturers prepared non-OBE-based learning tools. Third, 71.4% of lecturers need to learn about OBE-based learning tools. The education paradigm is changing from Input-Based to Outcome-Based Education (OBE). Education is reviewed and replaced with something more relevant, originally 'what is important for lecturers to teach' and has now changed to 'what is important for students to learn and master.' For this reason, it is necessary to develop OBE-based learning tools in core scientific subjects in Primary School Teacher Education Postgraduate Programs.